Reorienting the Gaze: Monstrous Bodies in Remediations of Frankenstein - Borham-Puyal , Miriam (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2023)
Visual adaptations of the Frankenstein myth highlight the role ocularcentrism and scopic power play. By engaging with the concept of the gaze, this paper analyzes remediations of Mary Shelley’s masterpiece and discusses how visual narratives frame potentially monstrous bodies in order to assimilate or question traditional privileged visions and their construction of otherness, as well as to (re) orient spectators towards recognition of or detachment from the onscreen monster. It will address particularly relevant examples: Edison’s Frankenstein, the YouTube series Frankenstein M.D., Whale’s and Branagh’s iconic remediations, as well as the less known Murders of the Rue Morgue and Frankenhooker. Ultimately, this work will vindicate the role of remediations as an arena within which contemporary imaginaries regarding otherness and who holds the visual and narrative power are either legitimized or challenged.